An analysis of education studies undergraduate students’ perception of ICT: a case study - Ioanna Palaiologou (Educational Futures)
The rapid increase in the use of ICT in education and the changing demands of the labour force requiring transferable skills provided by educational studies is an emerging reality. Even though in recent years there has been a upsurge of interest in the use of new technologies in higher education, there is as yet relatively little research on the ICT skills of undergraduate students in educational studies courses or how educational studies degrees can offer ICT skills to their students as a part of their study programme. Thus this research project was two fold. Firstly, it was intended to identify the ICT skills of Level 5 undergraduate students. The aim was to investigate students’ self perception of their ICT skills over a period of three months. Secondly, it aimed to investigate how students’ self perception changed over a module created to improve their ICT skills. The research project attempted to assess students’ self perception of their ICT skills using an ICT Audit test prior to and after the module had finished. The statistical nominal analysis of the ICT audit revealed that the Level 5 students with computer anxiety or less preparation for using computers are most at risk of not taking advantage of the wide range of universities ICT resources. However, the qualitative data revealed that these students overcame their computer anxiety when ICT is purposeful and contextualised.